Learning from the field : innovating China's higher education sys tem - Vernooy, Ronnie, 1963-; International Development Research Centre (Canada) (New Delhi : Cambridge University Press under the Foundation Books imprint ; Ottawa : International Development Research Centre, 2008)
Contributed articles.
Includes bibliographical references.
Keywords: Rural development; Natural resources -- Co-management -- Study and teaching -- China; Curricullum change -- China; Educational change -- China